2019
DOI: 10.3389/fphar.2019.00975
|View full text |Cite
|
Sign up to set email alerts
|

Ontological and Non-Ontological Resources for Associating Medical Dictionary for Regulatory Activities Terms to SNOMED Clinical Terms With Semantic Properties

Abstract: Background: Formal definitions allow selecting terms (e.g., identifying all terms related to “Infectious disease” using the query “has causative agent organism”) and terminological reasoning (e.g., “hepatitis B” is a “hepatitis” and is an “infectious disease”). However, the standard international terminology Medical Dictionary for Regulatory Activities (MedDRA) used for coding adverse drug reactions in pharmacovigilance databases does not beneficiate from such formal definitions. Our objective was to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…According to a survey conducted by the NLM, 49% of the UMLS users chose "facilitate mapping between terminologies" as their purpose [14]. Several studies have utilized UMLS as a tool to link different terminologies [10,11,[15][16][17][18][19]. Different from UMLS, OMOP provides a data model to map different vocabularies to a common standard.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a survey conducted by the NLM, 49% of the UMLS users chose "facilitate mapping between terminologies" as their purpose [14]. Several studies have utilized UMLS as a tool to link different terminologies [10,11,[15][16][17][18][19]. Different from UMLS, OMOP provides a data model to map different vocabularies to a common standard.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research has attempted to associate Med-DRA with SNOMED CT [5,11,15,16,18,26]. Bodenreider et al [26,27] utilized UMLS as a dictionary to study the mapping relationships between MedDRA and SNOMED CT. One study found that 64.6% of MedDRA preferred terms can be mapped to SNOMED CT [11].…”
Section: Introductionmentioning
confidence: 99%